2009
DOI: 10.1038/jid.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Destruction of Skin Melanocytes by Perilesional T Cells from Vitiligo Patients

Abstract: In vitiligo, cytotoxic T cells infiltrating the perilesional margin are suspected to be involved in the pathogenesis of the disease. However, it remains to be elucidated whether these T cells are a cause or a consequence of the depigmentation process. T cells we obtained from perilesional skin biopsies, were significantly enriched for melanocyte antigen recognition, compared with healthy skin-infiltrating T cells, and were reactive to melanocyte antigen-specific stimulation. Using a skin explant model, we were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
343
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(381 citation statements)
references
References 35 publications
21
343
1
5
Order By: Relevance
“…In the elicitation phase of vitiligo, triggers including physical trauma to the skin, emotional stresses, and imbalances of endogenous neural factors, metabolites or hormones lead to oxidative stress within melanocytes which then respond by actively secreting heat-shock protein 70 and chaperoned melanocyte antigens [6]. During the immune activation stage, -presenting dendritic cells with the subsequent activation and recruitment of anti-melanocyte autoreactive cytotoxic T lymphocytes to the skin [7] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the elicitation phase of vitiligo, triggers including physical trauma to the skin, emotional stresses, and imbalances of endogenous neural factors, metabolites or hormones lead to oxidative stress within melanocytes which then respond by actively secreting heat-shock protein 70 and chaperoned melanocyte antigens [6]. During the immune activation stage, -presenting dendritic cells with the subsequent activation and recruitment of anti-melanocyte autoreactive cytotoxic T lymphocytes to the skin [7] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have identified a pivotal role for cytotoxic T cells in inducing melanocyte-specific destruction in vitiligo [7], including the findings that CD8 + T cells isolated from vitiligo skin are cytotoxic to melanocytes, recognise melanocyte-specific autoantigens [7], and induce autologous melanocyte apoptosis through IL-6 and IL-13 [9] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…4,18,19) In vitiligo patients and animal models, IFN-γ level is significantly elevated in lesional skin. 4,20) IFN-γ signaling regulates the expression of cytokine as well as adhesion molecules facilitating the lymphocyte migration.…”
Section: Egcg Inhibited Janus Kinase (Jak)2 Activity In Vitromentioning
confidence: 99%
“…4,5) Moreover, immunosuppressive therapies targeting T-cell activation have been shown to be effective for vitiligo treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation